On the Application of Gas Discharge Plasmas for the Immobilization of Bioactive Molecules for Biomedical and Bioengineering Applications - Hempel, Frank; Steffen, Hartmut; Busse, Benedikt; Finke, Birgit; Nebe, J. Barbara; Quade, Antje; Rebl, Henrike; Bergemann, Claudia; Weltmann, Klaus-Dieter; Schröder, Karsten (IntechOpen, 2011)
None